2015
DOI: 10.1111/nph.13374
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of the Fusarium graminearum phosphatome

Abstract: Summary Phosphatases are known to play important roles in the regulation of various cellular processes in eukaryotes. However, systematic characterization of the phosphatome has not been reported in phytopathogenic fungi. The wheat scab fungus Fusarium graminearum contains 82 putative phosphatases. The biological functions of each phosphatase were investigated in this study. Although 11 phosphatase genes appeared to be essential, deletion mutants of the other 71 phosphatase genes were obtained and characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
118
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(124 citation statements)
references
References 80 publications
6
118
0
Order By: Relevance
“…Consistent with this hypothesis, ten proteins involved in the virulence or DON biosynthesis of F. graminearum were found to be acetylated, including 4 transcription factors, 4 protein kinases and 2 phosphatases (Table 1) [4143]. The MS/MS spectra and peak assignments for the acetylated peptides of these proteins were presented in Additional file 1: Figure S3.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Consistent with this hypothesis, ten proteins involved in the virulence or DON biosynthesis of F. graminearum were found to be acetylated, including 4 transcription factors, 4 protein kinases and 2 phosphatases (Table 1) [4143]. The MS/MS spectra and peak assignments for the acetylated peptides of these proteins were presented in Additional file 1: Figure S3.…”
Section: Resultsmentioning
confidence: 64%
“…The results of inoculation with the gene deletion mutant Δ Fg5894 and Δ Fg9532 , respectively showed that the virulence of the two mutants on wheat was significantly reduced. And further, DON biosynthesis defect was detected in the two mutants, in particular, there was no DON was detected in Δ Fg9532 [43]. It was found that most of the acetylation sites are located in the conserved/important domains of these ten proteins.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, genes related to pathogenesis and other responses have been identified. Special attention has been given to genes encoding proteins of the secretome [5861], kinome [62] and phosphatome [63]. However, little is known about which of those identified genes play an active role in explaining quantitative differences in aggressiveness among isolates occurring in natural populations, as the vast majority of studies have used only one Fusarium isolate.…”
Section: Discussionmentioning
confidence: 99%
“…A separate study that focused on kinases determined that the accessory genes FGSG_07812 , FGSG_11614 , and FGSG_02153 all contributed to toxin production while FGSG_03146 contributed to spore production and disease [50]. Disruption of a possible phosphatase regulatory subunit FGSG_11641 has also been shown to reduce disease accumulation [56]. Together, the accessory genome appears to contain genes that contribute to metabolic processes, as well as other processes potentially involved in development or disease.…”
Section: Resultsmentioning
confidence: 99%